Review study of refraction error measurement methods of human cornea - Nser H.Y.; Al-Sharify N.T.; Ahmed S.M.; Weng L.Y.; See O.H.; Al-Sharify Z.T.; Ghaeb N.H. (American Institute of Physics Inc., 2024)
This paper aims to comprehensively review the refractive error measurement theories in human cornea, which is considered one of the most important theories used in biomedical engineering applications on which ophthalmology diagnostic equipment depends. The policy used in this work are the extensive reading of published manuscripts in international scientific journal and the adoption of the mechanism of accurate transmission of established scientific facts in an easy and fluent manner. In comparison, this research revealed one of the reasons for the differences in results obtained for the same patient from various diagnostic equipment, these devices base their job performance on the sort of scientific theory established by the system. So, for every measurement theory of refractive error there is a set of determinants, and these determinants directly affect the way the theory implements its requirements, and thus we get a slight spectrum of variation in the results, but it leads to similar scientific constants. Therefore, conclude that the slight discrepancy in the value of a specific variable that is measured by more than one device is a natural result of the dependence of each device that used in diagnosing refractive errors on a specific physical theory, and that one of the main factors that influence the results of the refractive error measurement obtained from different devices. 2023 Author(s).